Ministry of Petroleum and Mineral Resources Decree No. 140 Of The Year 2023 The selling price of one liter of benzene / Ministry of Petroleum and Mineral Resources Decree No. 141 Of The Year 2023 The selling price of one ton of mazut having ordinary specifications / Ministry of Petroleum and Mineral Resources Decree No. 142 Of The Year 2023 The sale price per cubic meter of compressed natural gas = وزارة البترول والثروة المعدنية قرار رقم 140 لسنة 2023 سعر بيع البنزين / وزارة البترول والثروة المعدنية قرار رقم 141 لسنة 2023 سعر بيع المازوت / وزارة البترول والثروة المعدنية قرار رقم 142 لسنة 2023 سعر بيع الغاو الطبيعى المضغوط - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic